2008
DOI: 10.1074/jbc.m800261200
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine-scanning Analysis of Putative Helix XII in the YgfO Xanthine Permease

Abstract: Transmembrane helix XII of UapA, the major fungal homolog of the nucleobase-ascorbate transporter (NAT/NCS2) family, has been proposed to contain an aromatic residue acting as a purine-selectivity filter, distinct from the binding site. To analyze the role of helix XII more systematically, we employed Cysscanning mutagenesis of the Escherichia coli xanthine-specific homolog YgfO. Using a functional mutant devoid of Cys residues (C-less), each amino acid residue in sequence 419 ILPASIYVLVENPICAGGLTAILLNIILPGGY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
47
0
26

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(75 citation statements)
references
References 26 publications
2
47
0
26
Order By: Relevance
“…Segments of the YgfO sequence are shown as helical wheel plots of residues 259 -276 (TM8), 301-318 (TM9a), 329 -346 (TM9b), and 419 -436 (TM12). The four irreplaceable residues (Glu-272, Asp-304, Gln-324, Asn-325) (red), Asp-276, which contains an essential carboxyl group (red, underlined) and Asn-430, which is vicinal to the binding site (9) are enlarged and bolded and shown as targets. Sites of NEM-sensitive single Cys mutants are shown with a dark background, and highly sensitive sites (IC 50 Յ 30 M) are shown with bolder peripheries.…”
Section: Xanthinementioning
confidence: 99%
See 3 more Smart Citations
“…Segments of the YgfO sequence are shown as helical wheel plots of residues 259 -276 (TM8), 301-318 (TM9a), 329 -346 (TM9b), and 419 -436 (TM12). The four irreplaceable residues (Glu-272, Asp-304, Gln-324, Asn-325) (red), Asp-276, which contains an essential carboxyl group (red, underlined) and Asn-430, which is vicinal to the binding site (9) are enlarged and bolded and shown as targets. Sites of NEM-sensitive single Cys mutants are shown with a dark background, and highly sensitive sites (IC 50 Յ 30 M) are shown with bolder peripheries.…”
Section: Xanthinementioning
confidence: 99%
“…The other two irreplaceable residues of YgfO are in the neighboring helices TM8 (Glu-272) and TM9a (Asp-304) and appear to be implicated with the conformational changes following binding and/or coupling purine with proton translocation, but not with substrate binding per se (10). Apart from the irreplaceable ones, a number of other important residues have been found, including residues at the middle of helices TM1 (His-31) and TM3 (Asn-93), which contribute to determining the proper affinity and selectivity of the purine binding site (10), residues at the middle of TM12 (Asn-430, Ile-432), which are close to the binding site and/or optimize binding indirectly (9), and residues within or adjacent to the NAT motif which are important conformationally (Ala-323) (11) or involved in defining the optimal specificity profile (Thr-332, Gly-333, Ser-336) (8,11). Overall, residues delineated as crucial for the mechanism of substrate recognition and selectivity cluster primarily at the NAT motif region (Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We launched a systematic series of Cys-scanning and site-directed mutagenesis studies of YgfO to elucidate structure-function relationships in a bacterial NAT (9,10). In the course of these studies, we showed that the NAT motif sequence region of YgfO includes the essential determinants Gln-324, irreplaceable for high affinity binding and uptake; Asn-325, irreplaceable for active transport; and an ␣-helical stripe of residues (Thr-332, Gly-333, Ser-336, Val-339), highly sensitive to site-directed alkylation and important for ligand selectivity 3 (9).…”
mentioning
confidence: 99%